Post translational modification regulation of transcription factors governing pancreatic β-cell identity and functional mass - Wong, Alicia; Alejandro, Emilyn U. (Frontiers in Endocrinology, 2025)
Dysfunction of the insulin-secreting β-cells is a key hallmark of Type 2 diabetes (T2D). In the natural history of the progression of T2D, factors such as genetics, early life exposures, lifestyle, and obesity dictate an individual’s susceptibility risk to disease. Obesity is associated with insulin resistance and increased demand for insulin to maintain glucose homeostasis. Studies in both mouse and human islets have implicated the β-cell’s ability to compensate through proliferation and survival (increasing functional β-cell mass) as a tipping point toward the development of disease. A growing body of evidence suggests the reduction of β-cell mass in T2D is driven majorly by loss of β-cell identity, rather than by apoptosis alone. The development and maintenance of pancreatic β-cell identity, function, and adaptation to stress is governed, in part, by the spatiotemporal expression of transcription factors (TFs), whose activity is regulated by signal-dependent post-translational modifications (PTM). In this review, we examine the role of these TFs in the developing pancreas and in the mature β-cell. We discuss functional implications of post-translational modifications on these transcription factors’ activities and how an understanding of the pathways they regulate can inform therapies to promoteβ-cell regeneration, proliferation, and survival in diabetes.